2010
DOI: 10.1007/s11205-010-9747-8
|View full text |Cite
|
Sign up to set email alerts
|

National Income and Income Inequality, Family Affluence and Life Satisfaction Among 13 year Old Boys and Girls: A Multilevel Study in 35 Countries

Abstract: Adolescence is a critical period where many patterns of health and health behaviour are formed. The objective of this study was to investigate cross-national variation in the relationship between family affluence and adolescent life satisfaction, and the impact of national income and income inequality on this relationship. Data from the 2006 Health Behaviour in School-aged Children: WHO collaborative Study (N = 58,352 across 35 countries) were analysed using multilevel linear and logistic regression analyses f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 44 publications
(67 reference statements)
9
62
0
1
Order By: Relevance
“…Another study on macro-level determinants of young people's health has shown that both, low family affluence and high income inequality at the country-level were negatively related to subjective health [18]. Levin et al [30] showed that national income and income inequality were associated with life satisfaction, and socioeconomic inequalities were greatest in poorer countries and in countries with an unequal income distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study on macro-level determinants of young people's health has shown that both, low family affluence and high income inequality at the country-level were negatively related to subjective health [18]. Levin et al [30] showed that national income and income inequality were associated with life satisfaction, and socioeconomic inequalities were greatest in poorer countries and in countries with an unequal income distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Conceptual model. Effect of country-level (arrow 1) and cross-level interaction effects between individual socioeconomic and macro-level determinants (arrow 2) (modified according to Levin et al [30]). …”
Section: Introductionmentioning
confidence: 99%
“…Gobina et al (2008) used the binary high/ low form of the Cantril Ladder described above to examine the relationship between bullying and subjective health in Latvia and Lithuania. Levin et al (2011) used both the continuous life satisfaction score and binary measure to investigate socioeconomic inequalities in young people's life satisfaction across 35 countries, while Richter (2005) and Levin et al (2009) used a binary measure to examine inequalities in life satisfaction in Germany and Scotland respectively. Zambon et al (2006) also used the binary measure, to study the impact of social welfare regimes on socioeconomic inequalities in young people's life satisfaction across 32 countries, as did Molcho et al (2007), who found the relationship between health outcomes and life satisfaction using the Cantril Ladder to be similar to that using other life satisfaction measures among the Irish adolescent population.…”
Section: Use Of the Adapted Cantril Ladder In Published Researchmentioning
confidence: 99%
“…Studies have also demonstrated that LS is related to age, gender, material and housing circumstances, family and school environment, and socioeconomic status (6)(7)(8)(9)(10)(11)(12)(13). Furthermore, LS in adolescents is strongly influenced by life experiences, social relationships, stress and anxiety, social competence and good coping skills, self-esteem, self-acceptance, the ability to love oneself, optimism, and individual spirituality (7,8,14,15).…”
Section: Introductionmentioning
confidence: 99%